2017
DOI: 10.7600/jpfsm.6.317
|View full text |Cite
|
Sign up to set email alerts
|

Until it hurts? Epidemiology of musculoskeletal pain in youth sports

Abstract: Sports and physical activity provide multiple social and health benefits to participants, but may also increase the risk of developing musculoskeletal pain and injuries, especially in skeletally immature adolescents. This review outlines the 1) measurement and prevalence of musculoskeletal pain in adolescents, 2) dose-response relationship between the organized sports activity and musculoskeletal pain, 3) high risk population, based on our previously published epidemiological studies in Japan, and finally, 4) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…The adverse events were classified as 26 injuries, 13 falls, and six others. In a report on injuries during sports activities, Kamada et al 11) surveyed Japanese students (12-18 years of age) and reported that injuries occurred most commonly in the lower extremities (15.4%).…”
Section: (154)mentioning
confidence: 99%
See 1 more Smart Citation
“…The adverse events were classified as 26 injuries, 13 falls, and six others. In a report on injuries during sports activities, Kamada et al 11) surveyed Japanese students (12-18 years of age) and reported that injuries occurred most commonly in the lower extremities (15.4%).…”
Section: (154)mentioning
confidence: 99%
“…Reports of adverse events during sports activities included those involving athletes [3][4][5] and relatively high-intensity exercise, such as international athletic competitions [6][7][8] . They also included adverse events involving exercise therapy at medical institutions 9,10) , those involving local residents such as students 11,12) , and large-scale events such as marathons [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%